Work-Family Interface of Hospitality Industry in Malaysia: The Moderating Effects of Religiosity - Sim, Adriel; Bujang, S. (Canadian Center of Science and Education, 2012)
This paper highlighted the lack of studies that examined the relationship between work-family interface and job and family satisfaction in hospitality industry. Based on review of past research on work-family studies and related constructs, this paper discussed the development of propositions linking work-family conflict, work-family enrichment, job and family satisfaction. Next, the development of proposition to test the possible moderating effects of religiosity will also be discussed. The major theoretical, empirical and practical contributions of this study will also be highlighted and discussed. The conceptual model presented shed light on work-family research which could be used for future research in this area.